Boundary Issues in Counseling : multiple roles and responsibilities - Herlihy, Barbara; Corey, Gerald (American Counseling Association, 2014)
"This highly regarded book is essential reading for counselors struggling to find a clear personal position on the range of issues and questions that can arise with multiple relationships. It is also an ideal supplemental text for courses in ethics and professional practice, as well as for practicum and internship seminars to train the next generation of counselors"--Page 4 of cover